Entrepreneurial intention of university students: An analysis of gender and ethnic groups - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh (The International Journal of Knowledge, Culture and Change Management, 2009)
Is there any difference between entrepreneurial intention of university students in terms of their gender and ethnic groups? This study is among the few studies that attempt to find a response to this question on the context of three public universities in Malaysia. The sample comprised of students from Science and Social Science faculties. Findings illustrated that there was a significant difference between male and female students on entrepreneurial intention where the male students obtained higher mean score. Regarding to ethnic groups, it was found that there is no significant difference on the entrepreneurial intention of the Malay and non-Malay students. Further analysis was conducted and it was found that the Malay students’ mean scores are significantly different from non-Malay students on attitude towards entrepreneurial career, perceived behavioral control, and entrepreneurial efficacy. This paper discusses the findings and provides suggestions to improve entrepreneurial intention among university students.